Respuesta :
Answer:
D) [tex]d=\sqrt{(6-9)^2+(3-(-2))^2}[/tex]
Step-by-step explanation:
Distance between two points formula:
[tex]d=\sqrt{(x_2-x_1)^2+(y_2-y_1)^2}[/tex]
Given:
(x₂, y₂) = (6, 3)
(x₁, y₁) = (9, -2)
[tex]\implies d=\sqrt{(6-9)^2+(3-(-2))^2}[/tex]
Answer:
[tex]\large \textsf{d = $\sqrt{(6-9)^2+(3-(-2))^2}$}[/tex]
Step-by-step explanation:
Distance formula: [tex]\large \textsf {d = $\sqrt{(x_2-x_1)^2+(y_2-y_1)^2}$}[/tex]
Distance between the points (9, -2) and (6, 3):
- x₁ = 9
- x₂ = 6
- y₁ = -2
- y₂ = 3
[tex]\large \textsf {d = $\sqrt{(x_2-x_1)^2+(y_2-y_1)^2}$}\\\\\large \textsf{d = $\sqrt{(6-9)^2+(3-(-2))^2}$}\\\\\large \textsf{d = $\sqrt{(6-9)^2+(3+2)^2}$}\\\\[/tex]
Hope this helps!